Factors driving turnover and retention of information technology professionals - Korsakienė, Renata; Stankevičienė, Asta; Šimelytė, Agnė; Talačkienė, Milda (Journal of Business Economics and Management, 2014)
Taking into consideration turnover phenomenon and retention issues, the purpose of the paper is to reveal the employee perceptions on organisational and job-related factors impacting decisions to leave and to stay with the current employer. Based on theoretical discussion related to voluntary turnover and retention of employees, the research instrument was developed. A total of 143 responses were collected from employees working in private IT companies of Lithuania. The results revealed that base pay and challenging work content were perceived as the most important employment characteristics. Turnover prediction models disclose turnover intentions of project managers, which can be explained by participation in strategy development, support of top managers and negative perception of the base pay. Meanwhile, turnover intensions of heads of departments/ high level managers can be explained by negative associations with performance incentives/ bonuses, career opportunities and working conditions. The findings of the paper let us to develop theoretical insights and provide manager recommendations leading to the retention of information technology professionals.